The Birkin Effect: An Outside-In Perspective in the Brand Identity Matrix in Hermès' Heritage Branding - Rems,Christina-Maria; Maurer,Charlotte; Bergland,June (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose: The purpose of this paper is to examine how the personal stories and narratives attached to the Hermès Birkin bag intersect with the brand’s corporate storytelling to shape reputation and reveal a possible reversal of the Brand Identity Matrix. Design/methodology/approach: Qualitative research was conducted, using the case of Hermès and the Birkin bag. Secondary data was collected from online sources such as blog entries, forums, videos and interviews where consumers of the Birkin bag shared their personal stories, experiences and reasons for purchasing. In the next step a thematic analysis was conducted to identify and group recurring themes and patterns in the storytelling and to examine whether these narratives shape or influence reputation and perception of the Hermès brand. Findings: The findings of the study reveal that Hermès’ reputation is co-created through both internal heritage storytelling and external stories and narratives. Consumers value craftsmanship, timelessness and longevity that strengthens Hermès’ identity, while introducing new interpretations of the Hermès Birkin bag, such as investment value, personal milestone and status symbol. In the case of Hermès, Identity and Reputation form more of a circular flow rather than a linear process. Research limitations: The sample may not fully represent the diversity of Hermès customers or account for cross-cultural differences in consumer perceptions. Practical Implications: Managers should embrace consumer co-creation by facilitating storytelling spaces, and treat reputation as a shared strategic asset by integrating consumer narratives into ongoing brand communication. Originality/value: This paper extends Urde’s Brand Identity Matrix by introducing the concept of the Birkin Effect, demonstrating how external narratives in the luxury heritage sector can create an interplay between reputation and identity, a dynamic flow of co-creation. It contributes to literature on heritage branding, co-creating, and luxury brand management. Paper type: Research Paper
Keywords: Birkin Effect; Brand Identity Matrix; Storytelling; Heritage Branding; Co-Creation